2005
DOI: 10.1074/jbc.m501749200
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic CpG and Non-CpG Methylation of the Peg1/Mest Gene in the Mouse Oocyte and Preimplantation Embryo

Abstract: In somatic tissues, the CpG island of the imprinted Peg1/Mest gene is methylated on the maternal allele. We have examined the methylation of CpG and non-CpG sites of this differentially methylated CpG island in freshly ovulated oocytes, in vitro aged oocytes, and preimplantation embryos. The CpG methylation pattern was heterogeneous in freshly ovulated oocytes, despite the fact that they all were arrested in metaphase II. After short in vitro culture, Peg1/Mest became hypermethylated, whereas prolonged in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 25 publications
(24 reference statements)
5
69
1
2
Order By: Relevance
“…A study in human suggested aberrant DNA methylation at the imprinted H19 gene in oocytes following in vitro maturation (IVM) (Borghol et al, 2006) and prolonged IVM of mouse oocytes was associated with a loss of DNA methylation at Peg1 (Imamura et al, 2005). Another study reported aberrant DNA methylation at imprinted genes in oocytes after superovulation with high doses of gonadotrophins in mouse and human (Sato et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A study in human suggested aberrant DNA methylation at the imprinted H19 gene in oocytes following in vitro maturation (IVM) (Borghol et al, 2006) and prolonged IVM of mouse oocytes was associated with a loss of DNA methylation at Peg1 (Imamura et al, 2005). Another study reported aberrant DNA methylation at imprinted genes in oocytes after superovulation with high doses of gonadotrophins in mouse and human (Sato et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The hypermethylated pattern was maintained when time progressed to 21 and 29 h post hCG injection. By contrast, Imamura et al [46] reported that Peg1 lost methylation in oocytes during postovulatory aging. For Peg1, our result differed from that of Imamura et al [46].…”
Section: Dna Methylationmentioning
confidence: 98%
“…By contrast, Imamura et al [46] reported that Peg1 lost methylation in oocytes during postovulatory aging. For Peg1, our result differed from that of Imamura et al [46]. Such discrepancy may be due to different oocyte aging times, or different domains of the same gene examined.…”
Section: Dna Methylationmentioning
confidence: 98%
“…12 This preference supports previous gene-specific observations. [13][14][15][16][17][18][19][20][21] Interestingly, the CAG/CTG site preference of non-CpG methylation matches the sequence preference of some mammalian DNA methyltransferases. 22,23 Non-CpG methylation has typically been assessed using bisulfite sequencing, a method with which most labs are not familiar.…”
Section: Identification Of Restriction Endonucleasesmentioning
confidence: 99%